Genetic Deletion of TLR4 on Platelets Attenuates Experimental Pulmonary Hypertension - Bauer, Eileen M. (2014)
RATIONALE: Recent studies demonstrate a role for TLR4 in the pathogenesis of pulmonary hypertension (PH), however, the cell types involved in mediating the effects of TLR4 remain unknown. OBJECTIVES: The objective of this study was to determine the contribution of TLR4 expressed on nonparenchymal cells to the pathogenesis of PH. METHODS AND RESULTS: TLR4 bone marrow chimeric mice revealed an equal contribution of TLR4 on nonparenchymal and parenchymal cells in the pathogenesis of PH as determined by measuring right ventricular systolic pressure (RVSP) and right ventricular hypertrophy (RVH). However, deletion of TLR4 from myeloid lineage cells had no effect on the development of PH since we found no difference in RVSP or RVH in WT vs. LysM-TLR4−/− mice. To explore the potential role of platelet TLR4 in the pathogenesis of PH, platelet specific TLR4−/− mice were generated (PF4-TLR4−/− mice). TLR4 −/− platelets from either global TLR4−/− or PF4-TLR4−/− mice were functional but failed to respond to lipopolysaccharide (LPS) demonstrating a lack of TLR4. PF4-TLR4−/− mice demonstrated significant protection from hypoxia-induced PH, including attenuated increases in RVSP and RVH, decreased platelet activation, and less pulmonary vascular remodeling. Deletion of TLR4 from platelets attenuated serotonin release after CH and LPS stimulated platelets released serotonin and promoted pulmonary artery smooth muscle cell proliferation in a serotonin-dependent manner. CONCLUSIONS: Our data demonstrate that TLR4 on platelets contributes to the pathogenesis of PH and further highlights the role of platelets in PH.